Effects of a Peer-Tutorial Reading Racetrack on Word Fluency of Secondary Students With Learning Disabilities and Emotional Behavioral Disorders - Barwasser, Anne; Urton, Karolina; Grünke, Matthias (Frontiers in Psychology, 2021)
Reading difficulties that are not addressed at the primary level continue to exist at the secondary level with serious consequences. Thus, it is important to provide struggling students with specific reading support. In particular, many students with learning disabilities (LD) and emotional behavioral disorders (EBD) demonstrate reading obstacles and are at risk for motivation loss. The present study evaluated the effects of a motivational reading racetrack as peer-tutoring on the word reading skills of secondary students with LD with and without EBD. The intervention was conducted through 16-18 reading and 4-6 baseline units three times a week for 15 minutes over 8 weeks. The results showed positive effects with effect sizes up to 1.00. In addition, follow-up results were also promising. Our findings indicate that this multicomponent intervention has a positive effect on the word fluidity of low-achieving students in secondary education with LD and/or EBD.